Management of Recurrent Endometrial Cancer or Atypical Endometrial Hyperplasia Patients After Primary Fertility-Sparing Therapy - Chen, Junyu; Cao, Dongyan; Yang, Jiaxin; Yu, Mei; Zhou, Huimei; Cheng, Ninghai; Wang, Jinhui; Zhang, Ying; Peng, Peng; Shen, Keng (Frontiers in Oncology, 2021)
Objective: To evaluate the efficacy and prognosis of fertility-sparing re-treatment on patients with recurrent endometrial cancer (EC) and atypical endometrial hyperplasia (AEH) who wish to preserve their uterus after complete remission (CR) for primary conservative therapy. Methods: We performed a retrospective study on recurrent EC or AEH patients who received fertility-sparing re-treatment after achieving CR. Data regarding clinicopathological factors, adverse events, treatment efficacy, tumor prognosis, and reproductive outcome were analyzed. Results: Of the 98 recurrent patients with a median disease-free interval period of 19 (3-96) months, 18 patients decided to receive hysterectomy directly and 80 patients received fertility-preserving re-treatment. 71 (88.6%) cases achieved CR, 96.0% in AEH and 75.8% in EC patients, with the 6 (3-16) months median CR time. 7 (8.8%) patients failed to achieve CR, 1 PR，4 SD and 2 PD, then underwent the hysterectomy. 49 women attempted to get pregnant after CR and 13 (26.5%) became pregnant, 7 (14.3%) successfully delivered while 6 (12.2%) miscarried. During the follow-up period, 22 (31.0%) women had developed a second relapse with the median recurrence time of 12 (4-90) months and 10 patients decided to receive the third round of fertility-sparing treatment. 7 (70.0%) patients, 33.3% in EC and 85.7% in AEH, achieved CR again. Hysterectomy was performed in 2 (20.0%) patients due to SD. After the third-round treatment, 6 women had the desire to conceive but no one became pregnant successfully. Conclusion: For patients with recurrent EC and AEH after primary conservative treatment, fertility-preserving re-treatment can still achieve a promising response and patients have possibilities of completing childbirth.